A Randomized Pilot Study of Inositol in Association with Betaine and Boswellia in the Management of Mastalgia and Benign Breast Lump in Premenopausal Women - Pasta, Vittorio (Breast Cancer (Auckl), 2016)
Benign mammary lumps and mastalgia are the most common breast disorders; yet, there is no clear-cut consensus about the best strategy for their treatment. We hypothesized that a combination, including boswellic acid, betaine, and myoinositol, would be beneficial in breast disorders by exerting a pleiotropic effect on multiple pathways. Indeed, myoinositol has already been proven to modulate some factors involved in the genesis of breast diseases, such as fibrosis and metabolic and endocrine cues. In our study, 76 women were randomly assigned to either the experimental or the placebo arm. After six months of treatment, statistically significant differences between the two groups were recorded for pain relief (56% vs 17%) and breast density reduction (60% vs 9%). Furthermore, benign breast mass dimension showed a reduction in the experimental group (40% vs 16%). The combination of boswellic acid, betaine, and myoinositol has been demonstrated to be effective in the treatment of breast pain and radiologically and histologically confirmed benign breast mass and in the reduction of breast density, one of the pivotal risk factors for the development of breast cancer, without any side effects.